2022
DOI: 10.1371/journal.pone.0264140
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-based classification of bone tumors in the proximal femur on plain radiographs: System development and validation

Abstract: Purpose Early detection and classification of bone tumors in the proximal femur is crucial for their successful treatment. This study aimed to develop an artificial intelligence (AI) model to classify bone tumors in the proximal femur on plain radiographs. Methods Standard anteroposterior hip radiographs were obtained from a single tertiary referral center. A total of 538 femoral images were set for the AI model training, including 94 with malignant, 120 with benign, and 324 without tumors. The image data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Further patient demographics information is then combined together with the network outputs and given to a fully connected layer to obtain the final prediction. Another radiological-based DL analysis is conducted in [ 35 ], where samples of standard anteroposterior hip radiographs are exploited in order to classify autonomously the considered bone tumors. Several preprocessing steps are employed to stabilize and strengthen out the predictions of the evaluated architectures (ResNet, GoogleNet and EfficientNet).…”
Section: Related Workmentioning
confidence: 99%
“…Further patient demographics information is then combined together with the network outputs and given to a fully connected layer to obtain the final prediction. Another radiological-based DL analysis is conducted in [ 35 ], where samples of standard anteroposterior hip radiographs are exploited in order to classify autonomously the considered bone tumors. Several preprocessing steps are employed to stabilize and strengthen out the predictions of the evaluated architectures (ResNet, GoogleNet and EfficientNet).…”
Section: Related Workmentioning
confidence: 99%
“…Another report [30] on the detection of hip fracture using VGG16 with 3346 simple radiographs of 1773 fractured and 1573 nonfractured hips showed that the model and orthopaedic surgeons had accuracies of 95.5% and 92.2%, sensitivities of 93.9% and 88.3%, and specificities of 97.4% and 96.8%, respectively, indicating that the deep-learning model outperformed clinicians. Meanwhile, another study [24] reported the performances of CNN models and compared them against the performances of clinicians to classify proximal femoral bone tumors to determine the absence of tumor, benign tumors, and malignant tumors on plain radiographs. The diagnostic accuracy of the best-performing model, EfficientNet-bs, was higher than the mean accuracy of two general orthopaedic surgeons and two orthopaedic oncologists.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of cancers continues to rise [15, 25], improvements in diagnostic modalities, surgical techniques, radiotherapy, and systemic therapy have improved patient survival rates [19]. However, this improvement in survival in patients with advanced cancer has been accompanied by an increased probability of bone metastasis [8] and pathologic fractures, especially in the proximal femur [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence (AI) applications are popular in orthopedics for diagnosis and classification from radiography images. 1 ,2 Based on the results of these studies, the algorithms developed achieve near-perfect results. 3 It is important to conduct human comparison studies in order to translate this theoretical success into real-life medical practice.…”
Section: Introductionmentioning
confidence: 96%